Labial synechiae: a diagnostic conundrum - Kazmi, Zehra; Zaidi, Syed Zafar (Journal of the Pakistan Medical Association, 2023)
The purpose of this study was to shed some light on labial synechiae, which is a common yet unfamiliar condition seen initially by the family physician and ultimately by the paediatric urologist. It is often diagnosed incorrectly, leading to undue anxiety and stress for the unsuspecting parents, and results in multiple unnecessary lab investigations, hence, putting a burden on the healthcare system in general. After IRB approval, a retrospective chart review was performed over a period of 15 years (2007-2021), at The Indus Hospital, Karachi, Pakistan. The records of all female children who underwent examination under anaesthesia (EUA) for labial synechiae (n=29) were included in the study. Our results indicate that the primary healthcare physicians were unable to recognise labial adhesions at the time of initial presentation. —Continue